Portrait Of Psychological Well-Being In Single Parent Mothers: A Qualitative Case Study - Aulia Azkiyatul Wardah Priandini; Siti Nur Asiyah (International Conference on Sustainable Health Promotion, 2025)
This study aims to explore the psychological well-being (PWB) of single mothers, related to their experiences managing dual roles and the challenges of raising children independently. The study used a qualitative phenomenological-hermeneutic approach with purposive sampling, involving one 43-year-old participant who had been a single mother for eight years. Data were collected through in-depth interviews and anal yzed thematically. The results revealed six dimensions of PWB: self-acceptance, autonomy, positive relationships with others, purpose in life, environmental mastery, and personal growth. Participants demonstrated the ability to self-regulate, make independent decisions, manage emotions in relationships, prioritize children’s well-being, and continue to develop themselves. Self-efficacy, faith in God, and family support played a significant role in improving PWB of single mothers. These findings can form the basis for interventions to improve PWB of single mothers and the quality of life of their children.